Linking unfounded beliefs to genetic dopamine availability - Schmack, Katharina; Rössler, Hannes; Sekutowicz, Maria; Brandl, Eva J.; Müller, Daniel J.; Petrovic, Predrag; Sterzer, Philipp (Frontiers in Human Neuroscience, 2015)
Unfounded convictions involving beliefs in the paranormal, grandiosity ideas or suspicious thoughts are endorsed at varying degrees among the general population. Here, we investigated the neurobiopsychological basis of the observed inter-individual variability in the propensity towards unfounded beliefs. 109 healthy individuals were genotyped for four polymorphisms in the COMT gene (rs6269, rs4633, rs4818 and rs4680, also known as val158met) that define common functional haplotypes with substantial impact on synaptic dopamine degradation, completed a questionnaire measuring unfounded beliefs, and took part in a behavioural experiment assessing perceptual inference. We found that greater dopamine availability was associated with a stronger propensity towards unfounded beliefs, and that this effect was mediated by an enhanced influence of expectations on perceptual inference. Our results indicate that genetic differences in dopaminergic neurotransmission account for inter-individual differences in perceptual inference linked to the formation and maintenance of unfounded beliefs. Thus, dopamine might be critically involved in the processes underlying one's interpretation of the relationship between the self and the world.